Simulation Study on the Effect of Pre-cooling Quenching Process on Deformation of Half Axle Gear After Heat Treatment - Sun Siyuan; Tang Jinyuan; Tang Yalin; Liao Xianggui (Jixie chuandong)
Based on the material thermodynamics and heat treatment commercial simulation software,and taking the heat treatment process of the half axle gear of the automobile in a certain enterprise into account,the effect of pre-cooling quenching process on the deformation of the half axle gear is explored. The research takes20 Cr Mn Ti half axle gear as the research object,making use of JMat Pro software to establish the performance database of 20 Cr Mn Ti half axle gear and as well as DEFORM software to calculate the quantitative relationship between the process parameters of gear carburizing-quenching and pre-cooling quenching and the deformation after carburizing-quenching of the half axle gear. The study shows that,the overall deformation range of the side gear and the maximum deformation value can be reasonably controlled by selecting the optimized process parameters of gear carburizing-quenching and pre-cooling quenching. As for the half axle gear which studied,the taper of the deformation of the overall shaft hole after heat treatment can be reduced by 12. 9%,and the taper between the tooth end and the shaft end can be reduced by 12. 5%. The DEFORM software is an excellent tool for optimizing the heat treatment process and controlling the heat treatment deformation.